2004
DOI: 10.1111/j.1532-5415.2004.52215.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Pain That Was Excruciating at Some Time in the Previous Week: Prevalence, Characteristics, and Outcomes in Nursing Home Residents

Abstract: NH residents with daily pain that was sometimes excruciating were younger and seriously ill with functional decline and weight loss. Too often, persons remain in this level of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 32 publications
(51 reference statements)
2
62
0
Order By: Relevance
“…Research indicates that as many as 83% of nursing home residents experience pain that often goes unrecognized or inappropriately treated (AGS Panel, 2002;Teno, Kabumoto, Wetle, Roy, & Mor, 2004;Zanocchi et al, 2007). This is significant in that the presence of persistent pain adversely affects mood, sleep quality, functional ability, and quality of life (AGS Panel, 2002;Leong & Nuo, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that as many as 83% of nursing home residents experience pain that often goes unrecognized or inappropriately treated (AGS Panel, 2002;Teno, Kabumoto, Wetle, Roy, & Mor, 2004;Zanocchi et al, 2007). This is significant in that the presence of persistent pain adversely affects mood, sleep quality, functional ability, and quality of life (AGS Panel, 2002;Leong & Nuo, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pressure ulcers, malnutrition, and incontinence remains at unacceptable levels (IOM, 2001;Weiner et al, 2007). Of particular concern is the high number of nursing home residents who experience pain (AGS Panel on Persistent Pain in Older Persons [AGS Panel], 2002;Gibson, 2007;Zanocchi et al, 2007).Research indicates that as many as 83% of nursing home residents experience pain that often goes unrecognized or inappropriately treated (AGS Panel, 2002;Teno, Kabumoto, Wetle, Roy, & Mor, 2004;Zanocchi et al, 2007). This is significant in that the presence of persistent pain adversely affects mood, sleep quality, functional ability, and quality of life (AGS Panel, 2002;Leong & Nuo, 2007).…”
mentioning
confidence: 99%
“…6 Undertreated pain in nursing homes is well documented, 5 and roughly 4 percent of residents experience daily pain that is excruciating. 7 Pneumonia, infection, eating problems, and tube feeding are common and associated with high six-month mortality, distressing symptoms, and a high risk of hospitalization and medical intervention. 4 …”
Section: Standardizing Palliative Care In Nursing Homes: a Novel And mentioning
confidence: 99%
“…The prevalence of pain in patients living in nursing homes and community care is even higher (27.8%-86.5%). The highest rates are reported by patients who are able to self-report their pain (McClean & Higginbotham, 2002;Nygaard & Jarland, 2005;Takai, Yamamoto-Mitani, Okamoto, Koyama, & Honda, 2010;Teno, Kabumoto, Wetle, Roy, & Vincent, 2004;Torvik, Kaasa, Kirkevold, & Rustøen, 2009;Weiner & Hanlon, 2001). Torvik et al found a higher rate of pain among nonverbal patients when using the Doloplus-2, an observation-based pain assessment tool compared with self-reporting by patients in nursing homes.…”
mentioning
confidence: 99%